Closed diaphyseal fractures of femur in children treated by hip spica: early result of a clinical study - Ansari, M. A. Q.; Farhan, M. M.; Nayeemuddin, M. (International Journal of Research in Orthopaedics, 2017)
Background: Diaphyseal fracture of femur is a common injury in children with bimodal age distribution. The treatment modality of these fractures depend on several factors such as age of the patient, characteristics of the fracture– degree of displacement, location of fracture in femur, comminution, and open or closed injury. With the invention of titanium elastic nails, the recent trend in treating these fractures is by closed reduction and TENS, but the surgical management is not without complications hence we share our experience to reemphasize the role of hip spica cast immobilisation in treating these injuries. Methods: This is a prospective study of 30 cases of diaphyseal fractures of femur in children between the ages of 6 month to 6 years. History and mode of injury were recorded and complete physical examination was done. Plain anteroposterior and lateral radiographs confirmed diagnosis. Hip spica cast was applied under sedation or short general anesthesia. One and half spica was applied over thick padding with hip flexed 45 degrees abducted 30 degrees and external rotation of 10 degree. No attempt was made to obtain an end to end reduction. Patients were allowed to go home the same day after giving instructions regarding spica care. Follow up was done and radiographs were taken at 1, 2, 4 and 12 weeks. Any malunion– LLD, angulation or rotation were recorded. Results: The mean age of patients was 3.5 years (range 0.5 to 6 years). Of these 12 (40%) were male and 18 (60%) were female. The commonest mode of injury was fall while play in 73.33% (n=22) of patients. Mid shaft fractures are more common 53.33% (n=16) followed by upper third 40% (n=12). Average time for fracture union was 6 weeks (range 4-10 weeks). At one year all fractures healed in a satisfactory position without any LLD. Two patients had minor skin problems which were easily treated and cast continued. No stiffness of hip, knee or ankle was noted. Conclusions: Hip spica casting is an effective and reliable method for treating femoral shaft fractures in children with a union rate of 100%. The advantages of conservative treatment such as the avoidance of general anaesthesia on two occasions and the avoidance of surgery make a compelling argument in favour of this form of treatment.